Phytochemical Profiles and Anticancer Effects of Calophyllum inophyllum L. Extract Relating to Reactive Oxygen Species Modulation on Patient-Derived Cells from Breast and Lung Cancers - Jetsada Ruangsuriya; Jirapast Sichaem; Apichat Tantraworasin; Somcharoen Saeteng; Phanchaporn Wongmaneerung; Angkhana Inta; Neal M. Davies; Kewalin Inthanon (Scientifica)
Reactive oxygen species (ROS) contribute to cancer growth and metastasis. Using antioxidants to modulate cellular ROS levels is a promisingstrategy for cancer prevention and treatment. Calophyllum inophyllum L., or tamanu, is a medicinal plant renowned for its anti-inflammatory, antioxidant, and anticancer properties in traditional medicine systems. However, the anticancer effects of C. inophyllum extract on cellular ROS remain unexplored. This study represents the first report on such effects and provides the potential mechanisms underlying the anticancer properties of C. inophyllum extract. The branches of C. inophyllum were extracted, and the extract was comprehensively analyzed for phytochemical constituents, antioxidant capacity, total phenolic content, and total flavonoid content. Subsequently, the extract’s potential anticancer properties were evaluated using patient-derived cells from breast and lung cancer. The results revealed that the C. inophyllum extract possesses notable antioxidant activity and demonstrated no cytotoxicity within the initial 24 h of treatment. However, after 72 h, it exhibited significant antiproliferative effects. Moreover, the extract exhibited inhibitory properties against migration and invasion at concentrations below the IC50, which corresponded to the expression of related genes. Notably, these effects correlated with the reduction of intracellular ROS levels. Overall, our findings highlight the anticancer potential of C. inophyllum extract, emphasize its ability to modulate cellular ROS levels and target key molecular pathways involved in cancer progression. This study sheds light on the promising therapeutic implications of C. inophyllum extract as a novel agent for cancer treatment, which is safe for normal cells.